Building Early Religious and Moral Foundations through Al-Qruan Education Park : Study on TPQ Al-Hasanah, Tinjomoyo Village, Semarang City - Intan Sri Wahyuni; Ine Putri Setiawati; Novia Putri; Amilatus Sholihah; Nia Puspitasari; Ahmad Zakariyya; Iqbal Ainur Rofiq; Fuji Astutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education is a fundamental aspect in shaping the future generation of the nation, including in overcoming social problems such as ignorance and poverty. Through formal, non-formal, and informal education, individuals can develop their quality and capacity, including in terms of morals and religious values. Al-Hasanah Al-Qur'an Education Park (TPQ) in Semarang is one of the non-formal education institutions that aims to instill moral and religious values from an early age. This study uses a qualitative design to analyze teaching methods, parents' roles, challenges and solutions in the learning process at TPQ Al-Hasanah. Data were collected through direct observation, interviews with teachers, students and parents, and related documentation. The results show that teaching methods such as collective recitation of prayers, recitation of the Qur'an, and memorization of short surahs, accompanied by emotional support and parental involvement, are essential for the effectiveness of the learning process. However, challenges such as limited facilities, student absenteeism, and lack of parental support need to be addressed through the implementation of clear teaching methods, improved teacher competencies, and improved facilities. This research is expected to make a significant contribution to understanding the effectiveness of religious and moral learning programs and provide suggestions for improving the quality of education at TPQ Al-Hasanah.